2002
DOI: 10.1080/00221300209602103
|View full text |Cite
|
Sign up to set email alerts
|

Common Processes May Contribute to Extinction and Habituation

Abstract: Psychologists routinely attribute the characteristics of conditioned behavior to complicated cognitive processes. For example, many of the characteristics of behavior undergoing extinction have been attributed to retrieval from memory. The authors argue that these characteristics may result from the simpler process of habituation. In particular, conditioned responding may decrease during extinction partially because habituation occurs to the stimuli that control responding when those stimuli are presented repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 269 publications
5
69
0
1
Order By: Relevance
“…However, our results show systematic differences in the behaviour of the deer on typically busy and typically quiet days. Habituation to disturbance on frequently-used walking tracks has been documented in other wild animals, for example mule deer (Cornett et al 1979) and grizzly bears (Jope 1985), but repeated presentation of a stimulus does not necessarily lead to extinction of the response (McSweeney and Swindell 2002) and it seems unlikely that the deer in Glen Lui will stop responding to the walkers, since the herd has been feeding there for many years. Although we were not able to determine whether the deer suffered any increase in stress or change of diet composition in this study, the results suggest that, even in a situation where animals appear to be habituated to human disturbance, long-term population effects due to small but persistent changes in behaviour cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results show systematic differences in the behaviour of the deer on typically busy and typically quiet days. Habituation to disturbance on frequently-used walking tracks has been documented in other wild animals, for example mule deer (Cornett et al 1979) and grizzly bears (Jope 1985), but repeated presentation of a stimulus does not necessarily lead to extinction of the response (McSweeney and Swindell 2002) and it seems unlikely that the deer in Glen Lui will stop responding to the walkers, since the herd has been feeding there for many years. Although we were not able to determine whether the deer suffered any increase in stress or change of diet composition in this study, the results suggest that, even in a situation where animals appear to be habituated to human disturbance, long-term population effects due to small but persistent changes in behaviour cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A number of commonalities between habituation and extinction have been noted and used as the basis for an argument that the response decrement in both cases may arise at least partly through the same mechanism. [54][55][56][57] In the framework of associative theory, this sort of mechanism may be translated in terms of the degree to which the CS and/or US representations can be activated (Figure 2d -cf. Wagner 53 ).…”
Section: New Learningmentioning
confidence: 99%
“…That is, endogenous cannabinoid release is not a mechanism of fear extinction per se but rather occurs under conditions in which habituation occurs, which include, but are not specific to, extinction. The argument that extinction involves a significant habituation component is one that has been raised by several authors 54,56,57 (discussed earlier) and most recently was put forward by Kamprath and Wotjak, 55 who in a series of experiments demonstrated that mice exhibit freezing to a tone not only following tone-footshock pairings but also following exposure to footshock alone. In these experiments, mice were presented with one or more footshocks in a distinctive experimental context, then subsequently were placed into a different context and presented with a tone.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…For example, several studies investigating contextual control of extinction performance have demonstrated that responding to a CS can be renewed if the extinguished CS is tested in a context that differs from the extinction (i.e., treatment) context (see Bouton & Nelson, 1998, for a review). This research indicates that extinction does not erase conditioned associations but, instead, creates additional inhibitory associations that are highly context dependent (but see McSweeney & Swindell, 2002, for an alternative perspective). The clinical implication is that when an individual is exposed to alcohol cues in his or her natural environment following extinction of those same cues in a treatment context, a return, or renewal, of conditioned responding is likely.…”
mentioning
confidence: 99%